Model of nursing care for patients subjected to coronary angiography - Reczek, Agata; Brzostek, Tomasz; Gabryś, Teresa; Malinowska-Lipień, Iwona; Kawalec, Ewa; Gawor, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Coronarography allows to diagnose and localize the lesions in coronary arteries and estimate their severity. Like any other invasive procedure, it brings the risk of complications and side effects, both during and after the procedure. The purpose of this paper is to present a model of nursing care for patients undergoing coronary angiography.